A profile of 96 cases of penetrating injury of abdomen - Ramya, Chatragadda; Jayasree, Kasula (International Journal of Research in Medical Sciences, 2017)
Background: Trauma is a major health problem. Among various modes of trauma, penetrating trauma necessitates for immediate surgical intervention in most of the cases. Most commonly penetrating injuries in civilian group involves younger healthy population, who most productive and are very much responsible for the progress of the society and the country. Methods: This is a prospective study of 96 cases of penetrating injury to abdomen admitted to Gandhi Hospital, Secunderabad during the period August 2011 to September 2013. All the patients with history of penetrating abdominal trauma requiring admission during the study period are included in this study. All cases were evaluated for abdominal organ injury due to penetrating trauma by clinical and radiological criteria all cases were evaluated for abdominal organ injury due to stab. All the patients with peritoneal, evisceration, signs of peritonitis, shock underwent laparotomy. Results: 81 cases (84.3%) had significant abdominal injury requiring laparotomy. The criteria for laparotomy were evisceration (20.8%), shock (8.3%) and peritonitis (50%). Mere peritoneal penetration (83%) is a poor indicator of emergency laparotomy in stab injury. Erect X-ray abdomen is an unreliable criterion for laparotomy in presence of other signs. Conclusions: Majority of the patients required operative intervention particularly those with hemodynamic instability, generalized peritonitis, evisceration of omentum and bowel, and continuing haemorrhage. Peritoneal penetration as such is a poor indication of significant organ injury; hence it requires direct organ specific evaluation, such as computed tomography or laparoscopy to identify patients who can be safely treated without operations.